Age Specificity of Inbreeding Load in Drosophila melanogaster and Implications For the Evolution of Late-Life Mortality Plateaus - Reynolds, Rose M. (Copyright © 2007 by the Genetics Society of America, 2007)
Current evolutionary theories explain the origin of aging as a byproduct of the decline in the force of natural selection with age. These theories seem inconsistent with the well-documented occurrence of late-life mortality plateaus, since under traditional evolutionary models mortality rates should increase monotonically after sexual maturity. However, the equilibrium frequencies of deleterious alleles affecting late life are lower than predicted under traditional models, and thus evolutionary models can accommodate mortality plateaus if deleterious alleles are allowed to have effects spanning a range of neighboring age classes. Here we test the degree of age specificity of segregating alleles affecting fitness in Drosophila melanogaster. We assessed age specificity by measuring the homozygous fitness effects of segregating alleles across the adult life span and calculated genetic correlations of these effects across age classes. For both males and females, we found that allelic effects are age specific with effects extending over 1–2 weeks across all age classes, consistent with modified mutation-accumulation theory. These results indicate that a modified mutation-accumulation theory can both explain the origin of senescence and predict late-life mortality plateaus.